Frailty and associated factors of elderly Buddhist monks in Chiang Mai Province, Thailand - T, Ratanasiri; P, Lerttrakarnnon (Biomedical Sciences and Clinical Medicine, 2019)
Objective To determine the prevalence of frailty and identify factors associated with frailty in elderly Buddhist monks in Chiang Mai Province. Methods This cross-sectional descriptive study of elderly Buddhist monks (age ≥60 years) with a Barthel ADL score ≥12 living at temples in Muang District was conducted during the period 1 May through 30 June 2018. Each participating monk was interviewed and given a physical examination which included an assessment of frailty (using a modified version of the Fried’s Frailty Phenotype) as well as an assessment of their current health status. Factors potentially associated with frailty were analyzed using Chi-square test and Fisher’s exact test. Statistical analysis was done with SPSS for Windows version 22 software. Results Of the 135 elderly Buddhist monks, most (80.0%) were in a state of pre-frailty and 7.4% were in a state of frailty. Positive criteria for frailty were low grip strength (85.2%), self-reported exhaustion (17.8%), slow walking speed (17.0%), low level of physical activity (4.4%) and unintentional weight loss (3.0%). Diabetes mellitus, polypharmacy, hospitalization in the past year, and abnormalities in the heart or extremities were statistically significantly associated with frailty (p<0.05). Conclusion Most of the elderly Buddhist monks in the study were in a state of pre-frailty. Activities designed to increase grip strength and walking speed could potentially improve the health of these monks. A combination of frailty screening and comprehensive geriatric assessment should be used to evaluate the condition of each monk and identify appropriate treatment.